Relative age effect in the 2022–2023 World Fencing Championships - Bonito, Fabiana; Viães, Joana; Teles, Júlia; Flores, Luis A.; Iglesias, Xavier; Fragoso, Maria Isabel (Frontiers in Sports and Active Living, 2025)
IntroductionThis study aimed to investigate the presence of relative age effect (RAE) in the World Fencing Championships of the 2022–2023 season across three age categories.MethodsData from the participants of the World Fencing Championships were collected from the International Fencing Federation, resulting in a total of 2,791 participants distributed according to the age categories: 713 cadets, 1,048 juniors, and 1,030 senior athletes. The data collected included the athletes’ birthdate, birth quartile, sex, weapon, age category, country, continental area, and world championship result. An athlete’s relative classification was computed using their competition classification and the total number of participants in the event. The chi-square goodness-of-fit test was performed to assess the presence of RAE, examining differences in birth quarter distribution across the total sample, for each sex, and for the 18 events. Follow-up analyses included standardized residuals, Cramér's V effect size, and odds ratios. In events where RAE was detected, the Kruskal–Wallis and Quade's non-parametric ANCOVA tests were used to compare athletes’ relative classification across birth quarters.ResultsRAE was present, in the overall sample [χ2(3) = 16.142, p < 0.001, V = 0.044], according to sex [female: χ2(3) = 10.349, p = 0.016, V = 0.053; male: χ2(3) = 7.987, p = 0.046, V = 0.041], and was inconclusive when focusing on each event.DiscussionThe complexity of results in individual sports and the lack of research in fencing makes it difficult to understand the relevance of RAE in this sport. Despite the lack and inconsistency of results in fencing, coaches should be aware of this effect.